2015
DOI: 10.14257/astl.2015.114.09
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Consumers’ Discontinuance Intentions towards O2O Commerce: Focused on the Mediating Effects of Perceived Risk and User Resistance

Abstract: Abstract. With the development of telecommunication technologies, people can access the internet more immediately and easily at anytime and from anywhere. Along with this, e-commerce industry has also seen various innovations and rapid growth. Recently, a new type of e-commerce defined as O2O (Online to Offline), which combines great customer experience and excellent price competitiveness from offline and online commerce, has become the mainstream. Nevertheless, the O2O global industry is still in its prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Similarly, various intangible factors such as system availability and security affect customer perception of O2O. These findings resonate with Chi et al (2015) who suggested in their study that customers see perceive privacy violation, information uncertainty, annoyance, and negative social effect as the risks of adopting O2O, We thus argue that the success of O2O depends on allaying these concerns and focusing on understanding the benefits of O2O.…”
Section: Characteristics and Benefits Of O2osupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, various intangible factors such as system availability and security affect customer perception of O2O. These findings resonate with Chi et al (2015) who suggested in their study that customers see perceive privacy violation, information uncertainty, annoyance, and negative social effect as the risks of adopting O2O, We thus argue that the success of O2O depends on allaying these concerns and focusing on understanding the benefits of O2O.…”
Section: Characteristics and Benefits Of O2osupporting
confidence: 83%
“…Given its potential utility, researchers have started examining the relevant adoption and developmental issues with O2O from both customers and merchants' perspectives. From the customer perspective, one research stream has looked at the factors that drive O2O adoption and development (e.g., Chi et al, 2015), as these factors provide an understanding of behaviors and perceptions of customers. For instance, real time and loyalty program services have been found to drive customer adoption of O2O (Agusdin, 2016), pointing to the perceived value attached by the customers to the provision of online component in an O2O system.…”
Section: Characteristics and Benefits Of O2omentioning
confidence: 99%
“…Merchants began to launch all of their products/services on the platform, with online and offline businesses being fully integrated. This integration of online and offline shopping experiences was a welcome opportunity for the hundreds of thousands of local bricks-and-mortar retailers and regarded as one of the most profitable and successful e-business models (Chi et al 2015) The rapid development of O2O commerce in China is attribute to several factors. First, the high penetration of smartphones, mobile payment technology, 4G technology, and the location based service (LBS) imbedded in mobile devices in recent years provides technology support for O2O commerce (Zhou 2015).…”
Section: O2o Commerce In Chinamentioning
confidence: 99%
“…Information gathered through social relationships, such as one"s social group or mass media, has a large effect on a person"s decision making process [29]. With financial institutions and online companies suffering damages due to hacking, from time to time, numerous reports are distributed via various forms of mass media on concerns of information leakage and risks of security vulnerability.…”
Section: Negative Social Impactmentioning
confidence: 99%